Production of fine alumina from waste aluminum can - Wan Mohd, Wan Roslina; Purwanto, Hadi (2011)
Increasing the utilization of aluminum in daily life raises waste aluminum. At present, technology to process the scrap is a conventional process which consumes high energy and caused the environmental problem. An alternative technology has been proposed to process the waste aluminum can into valuable feedstock materials without release any emission. In this process, aluminum can was treated using alkaline solution in a closed reactor. Aluminum was easily dissolved into the solution and gas was spontaneously released. The results showed that the process was mainly controlled by temperature and concentration. The higher the temperature and concentration resulted in the faster of the dissolution process. At the end of the process, solution was filtrated and calcined at desired temperature. X-ray diffraction analysis revealed that the calcined filtrate contained of pure alumina. Particle size analysis results showed that calcination lead to produce finer particle of the alumina. Hydrogen gas also was produced as a main product that can be utilized as green energy source.